Determination of the X-ray Linear Attenuation Coefficient of Clay-Originated Bricks in Central Java Province, Indonesia - Ambrosius Karanggulimu; Edward Harefa (STKIP Singkawang, 2022)
The widespread use of radioactivity has culminated in adverse health consequences and has generated an entire health science study. It is established practice that certain precautions must be taken to avoid potential exposure to ionizing radiation like an x-ray. One way to control radiation hazards external is to use a radiation shield. In this study, clay-originated bricks were used as a shield and determine its linear attenuation coefficient of x-ray radiation. The bricks were collected from 5 regencies in Central Java province. Digital fluoroscopy was used as an x-ray radiation source and operated in 81 kV 32 mAs; also, it associated with the multi-purpose detector. It shows that linear attenuation coefficient of Boyolali, Klaten, Magelang, Temanggung, and Semarang bricks respectively are 0.8896 cm-1; 0.7455 cm-1; 0.7115 cm-1; 0.7254 cm-1; and 0.7972 cm-1. Furthermore, we calculate the half-value layer of each brick and indicates that brick from Boyolali is the most effective as a shielding among others that can reduce half value of x-ray radiation dose. This research is expected to enhance the systems integration of radiation shielding safeties and allow for the effective treatment of radiation sources for both humans and the environment.